2019
DOI: 10.1177/2325967119844821
|View full text |Cite
|
Sign up to set email alerts
|

Hip Function 6 to 10 Months After Arthroscopic Surgery: A Cross-sectional Comparison of Subjective and Objective Hip Function, Including Performance-Based Measures, in Patients Versus Controls

Abstract: Background: Little is known about hip-related function, mobility, and performance in patients after hip arthroscopic surgery (HA) during the time that return to sports can be expected. Purpose: To evaluate measures of subjective and objective hip function 6 to 10 months after HA in patients compared with healthy controls and to compare objective function in the HA group between the operated and nonoperated hips. Study Design: Cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…However, just half of all athletes undergoing hip arthroscopy return to their pre-injury sport and one in five returns to previous performance levels [ 6 , 22 ]. Recent research suggests that physical impairments alone cannot explain these low RTS rates, or the marked impairments in self-reported function observed in these patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, just half of all athletes undergoing hip arthroscopy return to their pre-injury sport and one in five returns to previous performance levels [ 6 , 22 ]. Recent research suggests that physical impairments alone cannot explain these low RTS rates, or the marked impairments in self-reported function observed in these patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of this chapter are very similar to another recently published study [240] that assessed hip strength, ROM and PROMs in an FAIS population at an average of eight months post arthroscopy.…”
Section: Chapter Reviewsupporting
confidence: 85%
“…Worner et al [240] also found flexion strength, internal rotation ROM and PROMs were significantly less than matched controls. However, the lack of pre-surgical assessment made it impossible to determine if strength or ROM had changed following the intervention of arthroscopy and subsequent rehabilitation.…”
Section: Chapter Reviewmentioning
confidence: 89%
“…Studies that present measurements of muscle strength and range of motion often compare postsurgery patients with clinical controls [ 30 , 31 , 32 ]. Most of the available literature provides an account of patients’ states before and after surgical intervention [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that hip flexion strength and passive range of motion of flexion remained reduced. There was a significant difference in the flexion ROM between the operated limb and nonoperated limbs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%